(untitled) - Surinder Pal Singh; Kailash Meena; Chungath Jain (Asian Journal of Medical Research, 2020)
Background: Both smoking and diabetes are attributed to be strongly linked with pulmonary tuberculosis. The significance of the study lies in assessing severity of manifestations in pulmonary tuberculosis patients due to smoking and diabetes. Subjects and Methods:This is a cross sectional observational study among patients presenting to Department of Tuberculosis and Chest Diseases, Government Medical College, Patiala.  200 Patients were enrolled in this study who are sputum smear positive pulmonary kochs patients already on ATT and admitted in this department were evaluated by clinical history, blood and radiological investigations and the data was statistically analyzed.Results:Non smoker non diabetic group had maximum of females, n=28(56%), whereas purely diabetic study group has maximum of males, n=30(60%).The total number of patients whose sputum showed bacterial culture was 19 (9.5%). In the patients having both diabetes and smoking as risk factor there was maximum culture positivity, n=6 (31.5%)and most common organism isolated was klebsiella pneumonia, n=3 (50%), Klebsiella was also the most common organism isolated overall, n=10 (62.5%).Conclusion: The combination of smoking and diabetes can lead to serious disease, sputum positivity and complications.